High dielectric constant composite films with high strength, toughness and thermal stability. (March 2016) - Zhu, Shi Sheng; Li, Wen Lei; Lin, Yu Jin; Zhang, Shu Ling
The dielectric properties of composite films comprising poly(ether ether ketone) (PEEK) and multiwalled carbon nanotubes (MWCNTs) wrapped in poly(ether sulphone) were investigated. These wrapped-MWCNT–PEEK composite films were fabricated through melt blending and subsequent melt extrusion. At low frequencies, the dielectric constant ( k ) of the composite PEEK film with 0.68 vol%-wrapped MWCNTs increased with the frequency, with the value of k being as high as 367 at 10 3 Hz. The wrapped-MWCNT–PEEK composite films also exhibited superior mechanical and thermal properties. In particular, the tensile strength and elongation at break values of all the composite films were greater than 103 MPa and 170%, respectively, and their 5% weight loss temperatures were higher than 575°C. This was attributable to the high conductivity of the MWCNTs, the uniform dispersion of the wrapped MWCNTs in the PEEK matrix, the strong interfacial adhesion between the wrapped MWCNTs and the PEEK, and the processing method employed, namely, melt extrusion.